DIGITAL LITERACY AS THE BASIS OF A DIGITAL SOCIETY - Babaeva Sabinabonu Davronbek kizi (Western European Studies, 2025)
Digital literacy is becoming a key prerequisite for sustainable socio-economic development and the formation of a digital society. In the context of the rapid spread of technology accelerated especially during the COVID-19 pandemic the acquisition of digital competencies has become essential. This article examines the essence and structure of digital literacy, its role in shaping the digital society, the impact of the pandemic as a catalyst for digitalization, as well as measures taken by the government, including the Presidential Decree on the Year of the Digital Economy. Particular attention is given to issues of education, digital inequality, and the formation of new professional competencies
Keywords: digital literacy; digitalization; digital society